2014
DOI: 10.1097/mpg.0000000000000389
|View full text |Cite
|
Sign up to set email alerts
|

Lutein and Preterm Infants With Decreased Concentrations of Brain Carotenoids

Abstract: These data reveal preferential accumulation and maintenance of lutein in the infant brain despite underrepresentation in the typical infant diet. Further investigation on the impact of lutein on neural development in preterm infants is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
171
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(178 citation statements)
references
References 34 publications
5
171
0
1
Order By: Relevance
“…With regards to the level of carotenoids in the brain, there was an interesting study by Vishwanathan et al (2014b) that provided the first data on the distribution of carotenoids in the infant brain and compare concentrations in preterm and term infant. The study was done on pre-existing voluntarily donated samples that were obtained from a federally-funded brain tissue bank.…”
Section: The Role Of Lutein On Infant Nutritionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regards to the level of carotenoids in the brain, there was an interesting study by Vishwanathan et al (2014b) that provided the first data on the distribution of carotenoids in the infant brain and compare concentrations in preterm and term infant. The study was done on pre-existing voluntarily donated samples that were obtained from a federally-funded brain tissue bank.…”
Section: The Role Of Lutein On Infant Nutritionmentioning
confidence: 99%
“…Currently, there are many evidences of the role of DHA on the retina and on the brain at molecular and signaling levels (Bazan et al, 2011). Despite this, there are two differences: on the one hand, there is always some DHA in tissues however it was reported that a few infants had no detectable levels of carotenoids (Vishwanathan et al, 2014b). On the other hand, DHA can be synthetized from alpha-linolenic acid while lutein can not be synthetized and must be taken with the diet.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Carotenoids play extremely important roles in maintaining normal physiological activities and against stress conditions in algae [5]. Carotenoids can serve as a light-absorbing molecule to absorb light wavelength at 400-500 nm, where chlorophyll has a weak absorption there [6,7]. Exception for that, in algae cell, carotenoids also participate in the synthesis of some protein complex.…”
Section: Introductionmentioning
confidence: 99%
“…In a unique study using cadaveric brain samples, Vishwanathan et al demonstrated that lutein was the predominant carotenoid in the infant brain, specifically in the frontal cortex, hippocampus, auditory cortex, and occipital cortex, during the first year of life [15]. Another study conducted by Wang et al indicates that lutein directs differentiation of cultured human stem cells into neural progenitor cells [16].…”
Section: Vitamin a In The Neonatementioning
confidence: 99%